In work, at home : towards an understanding of homeworking - Felstead, Alan, 1963- (Routledge, 2000)
More and more people are choosing to earn a living at home. In Work, At Home explores the meaning and experience of this type of employment by covering a wide range of issues including:* social relationships* current research methodologies* statistical analyses of global labour markets* the emotional and psychological processes of self-management* home relations. Presenting statistical analyses of labour markets in North America, Europe, Asia and Australia, In Work, At Home provides a valuable introduction to the issues and debates surrounding homeworki.